Development of objective method for wage correction of the chief engineers at mining stations of coal mines - Пістунов, Ігор Миколайович; Пономаренко, Павло Іванович; Пономаренко, Олексій Павлович (Technology audit and production reserves, 2016)
Type of the needs of workers and managers and ranking of the types in different categories of workers at the mines of Donetsk coal basin weren’t identified and accounted. So, it wasn’t used another means of increasing productivity. A survey of 64 main managers of Donbas mines was defined a list of the needs of the mine workers. The ranking values of these needs were defined. 342 workers of Western Donbas mines, who also gave a similar reply to the questionnaire, were interviewed. Comparing of ratings for managers and workers showed that they are differed. It was hypothesized that the more accurately chief engineers of mining stations know the needs of their workers, the more effective the work of this station. Formula for calculating decrease of bonus payment for chief engineers depending on the measure of non-concurrence in chief manager assessments of the needs of their workers and the workers themselves was proposed in order to encourage chief engineers. The calculation showed that the value of the discount may be small, but should encourage the chief managers of stations is better analyzing the needs of their employees, which will increase production or reduce the wage fund.